THE JURIDICAL REVIEW OF PROPERTY STATUS OVER THE ASSETS OF AN INDIVIDUAL CORPORATION UNDER POSITIVE LAW AND ITS’ IMPACT ON THE INDONESIAN ECONOMY - Kusumadjaja, Brilianto Putra; Ngaisah, Siti (YURIS: Journal of Court and Justice, 2025)
The Indonesian government has been actively facilitating business operations for both domestic and foreign entrepreneurs, as evidenced by the enactment of Law No. 6/2023, which amends the previous Job Creation Law (Law No. 2/2022) to enhance the business environment in Indonesia. Despite the positive intentions behind the Job Creation Law, there exists a vagueness in the norms regarding property rights for individual companies. This uncertainty has led to confusion among business actors and government officials, particularly concerning the issuance of land rights certificates. The primary aim of this research is to analyze and compare the impact of individual companies, as introduced by the Job Creation Law, on Indonesia's economy. The study seeks to clarify the legal position of property rights over individual company assets and their implications for the national economy. This research employs a normative juridical legal research methodology, utilizing a statutory approach and a conceptual approach. The authors examine relevant laws, regulations, literature, and articles to understand the legal framework surrounding property rights and their economic impact. The findings indicate that individual companies, as part of the Job Creation Law, have a positive influence on Indonesia's national economy. The contribution of micro and small enterprises (MSEs) to the Gross Domestic Product (GDP) has been significant, with their share increasing over the years, demonstrating their vital role in economic stability and growth.